Complications in the study of ancient tuberculosis: Presence of environmental bacteria in human archaeological remains. (April 2016) - Müller, Romy; Roberts, Charlotte A.; Brown, Terence A.
Abstract: There are many reports of ancient DNA from bacteria of the Mycobacterium tuberculosis complex (MTBC) being present in skeletons with and without osteological indications of tuberculosis. A possible complication in these studies is that extracts might also contain DNA from the microbiome of the individual whose remains are being analysed and/or from environmental bacteria that have colonised the skeleton after death. These contaminants might include 'mycobacteria other than tuberculosis' (MOTT), which are common in the environment, but which are not normally associated with clinical cases of tuberculosis. In this paper we show that MOTT of various types, as well as bacteria of related genera, are present in most if not all archaeological remains. Our results emphasise the complications inherent in the biomolecular study of archaeological human tuberculosis. The specificity of any polymerase chain reaction directed at the MTBC cannot be assumed and, to confirm that an amplification is authentic, a sequencing strategy must be applied that allows characterisation of the PCR product. Any variations from the reference MTBC sequence must then be checked against sequence data for MOTT and other species to ensure that the product does actually derive from MTBC. Our results also illustrate the challenges faced when assembling MTBC genome sequences from ancient DNA samples, as misidentification of MOTT sequence reads as MTBC would lead to errors in the assembly. Identifying such errors would be particularly difficult, if not impossible, if the MOTT DNA content is greater than that of the authentic MTBC. The difficulty in identifying and excluding MOTT sequences is exacerbated by the fact that many MOTT are still uncharacterized and hence their sequence features are unknown. Highlights: DNA from mycobacteria other than tuberculosis is present in archaeological bones. DNA from bacteria of related genera are also present. These bacteria have DNA similarities with the Mycobacterium tuberculosis complex. Polymerase chain reactions directed at the latter can give false-positives.